In vitro micrografting as an innovative strategy for the vegetative propagation of algarrobo blanco (Neltuma alba) - Carloni, Edgardo José; Rodriguez, Milena Nahir; Verga, Anibal; Grunberg, Karina (Springer, 2025)
Neltuma alba (Formerly Prosopis alba), known as ‘algarrobo blanco,’ is a native species of great biological, productive, and cultural importance in the phytogeographic regions of the Gran Chaco and the Espinal. However, it faces severe conservation threats due to deforestation and unsustainable management of native forests. In this context, vegetative propagation through in vitro micrografting emerges as an innovative strategy for preserving forest genetic resources. This study aimed to develop a vegetative propagation system based on in vitro micrografting and evaluate its feasibility in adult N. alba trees. Twelve-day-old in vitro-grown seedlings were used as rootstocks (etiolated vs. non-etiolated). Lateral buds were collected from current-year branches of adult trees, and the micrografts were cultured on MS medium supplemented with 0.1 mg L−1 of either BAP, IBA, or GA₃ individually. A Control treatment without growth regulators was also included. Apical micrografts sprouted from the second week onwards. Anatomical studies confirmed vascular reconnection between the scion and rootstock. Sprouting frequency was influenced by the season and hypocotyl type, although growth regulators showed no significant effect. During summer, the probability of contamination was higher than in spring. Ex-vitro acclimatization showed no differences between rootstock types, but IBA treatment increased survival rates. These results demonstrate that in vitro micrografting is a novel and promising tool for the vegetative propagation of adult N. alba trees.